Simulation of impact and fragmentation with the meshless methods - (:unkn) unknown (My University, 2010)
High velocity impact and penetration problems include large deformation, erosion, high strain rate dependent nonlinear material behavior and fragmentation. Therefore, meshless methods seem to be ideally suited for the modeling of penetration events as they allow unrestricted deformation and easy tracking of material interfaces and loading histories. In the first part of this study, a brief overview about meshless methods is given. Also the most important features of meshless methods with respect to mesh based approaches are compared. In the second part, numerical model is developed using one of the most frequently used meshless method, Smoothed Particle Hydrodynamics (SPH). 3D numerical simulations are performed on a high performance computer using MPP version of the explicit finite element code LS-Dyna. For reasonable behavior of material response under dynamic loading, Johnson Cook material models for armor steel target and 7,62 armor piercing projectile are derived using SHPB (Split Hopkinson Pressure Bar) test data. SPH computational investigation is compared with available experimental data such as penetration depth and impact crater diameter. For the future work, other potential meshless methods for ballistic impact problems are identified. Copyright © 2010 by ASME.